HPV detection in oral carcinomas - Aurora Karla de Lacerda Vidal; Arnaldo de França Caldas Júnior; Roberto José Vieira de Mello; Virgínia Ribes A. Brandão; Getúlio Isidoro da Rocha; Eliane Taromaru (Sociedade Brasileira de Patologia Clínica, 2004)
The authors set out in this study to verify the presence of low- and high-risk DNA of human papillomavirus (HPV) in oral cancer by means of the hybrid capture Digene® test (São Paulo-SP, Brazil) in smears from exfoliative cytology and also to compare the findings with those of conventional light microscopy (hematoxylin-eosin (HE)/Papanicolaou). Forty individuals gave their written informed consent to participate in the study and also had their clinical data analyzed. The 40 exfoliative cytology examinations performed to date produced the following results: 29 (72.5%) negative for low- and high-risk HPV-DNA; nine (22.5%) positive for low- and high-risk HPV-DNA; one (2.5%) positive for low-risk HPV-DNA; and one (2.5%) positive for high-risk HPV-DNA. There was agreement among the findings for the presence of DNA-HPV for both exfoliative cytology (smear to hybrid capture Digene® test and the cytological smear readings made by conventional light microscopy). It was therefore concluded that the HPV virus may be a cocarcinogen of the mouth cancer as it is in the cervix cancer.